Implementasi Program Csr Dalam Peningkatan Kesejahteraan Masyarakat Melalui Pengembangan Ukm Di Pamekasan - Nurul Alfian; Runik Puji Rahayu (Fakultas Ekonomi, Program Studi Akuntansi, 2019)
This study aims to see how much the implementation and role of Corporate social responsibility (CSR) in increasing the independence and welfare of the community through the development of SMEs in Pamekasan. This research uses a descriptive method with a qualitative approach. In qualitative research the researcher studies various selected issues, cases, and events in depth and in detail. The results of this study are in the CSR program run by the East Java UMKM Livestock Office stating that in addition to providing funding assistance to the UKM, it turns out that the CSR program from the East Java UMKM Bank provides training and guidance to the guided SMEs. Moreover, there are many problems that occur in SMEs, especially in Pamekasan Regency, so it can be concluded that it can help SMEs in improving the welfare and independence of the community through the development of SMEs.